THE FEATURES AND TYPES OF COMPLIMENTS IN ENGLISH LITERATURE (Ta'limning zamonaviy transformatsiyasi, 2024)
Compliments in English literature play a crucial role in character development, thematic exploration, and narrative progression. This article delves into the multifaceted features of compliments, such as their expressiveness, cultural context, and dual meanings, while also categorizing the various types of compliments, including sincere, ironic, flattering, backhanded, and romantic. Through examples from renowned literary works, this study highlights how compliments serve as more than mere polite exchanges but are crucial for understanding societal norms, interpersonal dynamics, and authorial intent.